Let's break down the equation \( -3(14c+4)+5= -12c-7 \) step by step and fill in all the missing terms and descriptions.
-
Start with the original equation: \[ -3(14c+4)+5= -12c-7 \]
-
Apply the distributive property: \[ -42c - 12 + 5 = -12c - 7 \]
-
Combine like terms: \[ -42c - 7 = -12c - 7 \]
-
Next, we can add 7 to both sides: \[ -42c = -12c \]
-
Now, add \(12c\) to both sides: \[ -42c + 12c = 0 \] Which simplifies to: \[ -30c = 0 \]
-
Next, divide both sides by \(-30\): \[ c = 0 \]
Now, we can piece together the explanations and steps filled in:
- Apply the distributive property (Step where we apply \(-3\) to \(14c\) and \(4\))
- Combine like terms (Combining \(-12\) and \(5\))
- Add \(7\) to both sides (getting rid of the \(-7\) on the right side)
- Add \(12c\) to both sides (moving \(-12c\) from the right to the left)
- Divide both sides by \(-30\) (to isolate \(c\))
So the missing answers would be:
- \(42c-\) (completed term)
- \(12c-7\) (completed term)
- Add 7 to both sides (correct operation)
- Subtract 12c from both sides (correct operation)
- Combine like terms (correct operation)
- \(c=\) (completed term)
- Divide both sides by \(-30\) (correct operation)
This completes the solving process correctly and fully. The final solution stated that \(c = 0\).